To simplify 9(k+13)+10(12k−1), we can distribute the coefficients to each term inside the parentheses:
9(k+13) + 10(12k-1)
= 9k + 9(13) + 10(12k) + 10(-1)
= 9k + 117 + 120k - 10
= 9k + 120k + 117 - 10
= (9k + 120k) + (117 - 10)
= 129k + 107
So, the simplified expression is 129k + 107.
Use the properties of operations to add 9(k+13)+10(12k−1)
14k-7
14k+13
19 1/2k-2/3
14k- 2/3
3 answers
thats not an options
My apologies for the confusion. Let's simplify the expression further:
9(k+13) + 10(12k-1)
= 9k + 9(13) + 10(12k) + 10(-1)
= 9k + 117 + 120k - 10
= 9k + 120k + 107
= (9k + 120k) + 107
= 129k + 107
So the simplified expression is 129k + 107.
9(k+13) + 10(12k-1)
= 9k + 9(13) + 10(12k) + 10(-1)
= 9k + 117 + 120k - 10
= 9k + 120k + 107
= (9k + 120k) + 107
= 129k + 107
So the simplified expression is 129k + 107.